HIGH TIBIAL OSTEOTOMY IN THE TREATMENT OF PATIENTS WITH STAGE II–III OF KNEE OSTEOARTHRITIS. IMMEDIATE RESULTS AND FACTORS INFLUENCING THE OUTCOME - V. E. Byalik (Научно-практическая ревматология, 2018)
Knee osteoarthritis (OA) is the most common form of OA. Medical treatment for OA does not provide the desired effect in a significant proportion of patients. With greater rates of knee OA and its rejuvenation, high tibial osteotomy (HTO) that can prolong the period of the patient’s own knee joint (KJ) function and postpone or completely avoid total knee arthroplasty is becoming increasingly relevant. Objective: to investigate the efficiency of HTO for stage II–III knee OA and the impact of age, body mass index (BMI), and correction angle on the immediate result of surgery. Subjects and methods. Thirty-five HTOs were carried out in 32 patients in 2003 to 2016. The male and female ratio was approximately 2:1. The patients’ mean age was 59.0±13.1 years; BMI, 29.04±3.57 kg/m2 , correction angle, 12.5±2.78°. A visual analog scale (VAS) was used to assess pain; and the Knee Society Score (KSS) was employed to rate the functional and objective status of the KJ. The degenerative process was graded using the Kellgren–Lawrence radiographic classification. Results and discussion. HTO proved to be effective in patients with both Stage II and III knee OA. A year after surgery, there was a substantial reduction in VAS pain (from 72.27±11.79 to 7.72±6.62 mm) and an improvement in functional and objective KSS scores (from 43.66±11.5 and 54.39±11.77 to 86.51±10.86 and 81.93±6.65 mm, respectively). The results were excellent (36.4%), good (57.6%), and satisfactory (6%). No X-ray signs of progressive OA were revealed one year after surgery. BMI affected immediate results (Spearman correlation coefficient = -0.34; p < 0.05). Thus, HTO has been established to be more effective in Stage II knee OA than in its Stage III. Age and correction angle do not affect immediate results while higher BMI is associated with worse outcomes and complications.